(untitled) (KYAMC Journal, 2021)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder of motor neurons and their axons characterized by signs of upper and lower motor neuron dysfunction. ALS has been associated with exposures in so called electrical occupation. We have found two young patient who developed features of MND following electrocution within 1 year. Due to this great diversity of possible causing agents for ALS, new researches are necessary to elucidate possible etiologies for a better approach to the patients, promoting preventive programs for the disease, optimizing functions and improving the life quality of the patients. A number of studies have demonstrated cognitive performance deficits following electric injury observed cognitive symptoms and neurobehavioral defecit. As treatment approach rehabilitation is important part of treatment as pharmacological part didn’t prove strong recovery. As MND causes high level of disability and dependency on caregiver causes gap in rehabilitation due to psychological issue. Neuropalliative rehabilitation is more important in these patient which is unavailable in our country. KYAMC Journal Vol. 11, No.-4, January 2021, Page 218-221